1988
DOI: 10.2334/josnusd1959.30.44
|View full text |Cite
|
Sign up to set email alerts
|

Functional forces on complete dentures during swallowing and mastication.

Abstract: In this study, the functional forces acting on maxillary complete dentures during mastication and swallowing were determined from three different locations by means of strain gauges. It was found that the functional forces caused by swallowing are quite marked in themselves and can cause deformation of the denture base resulting in undesirable force on the denture-bearing tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…One explanation might be that a greater volume of water (5 ml) required more lip activity to swallow compared to the amount of saliva, on average !-2ml (Kapur & Garrett, 1984;Christiansen, 1988), produced by the patients for the swallow. A weaker activity of the anterior temporal muscle in swallowing water Shan in swallowing saliva is in accordance with findings in a previous study of the swallowing activity of jaw closing muscles (Tallgren & Tryde, 1991. In this connection it is interesting to note that Pamir & Kalipcilar (1988) in strain gauge measurements of functional forces on the complete upper denture found that lesser forces were excerted during swallowing water than during swallowing saliva.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One explanation might be that a greater volume of water (5 ml) required more lip activity to swallow compared to the amount of saliva, on average !-2ml (Kapur & Garrett, 1984;Christiansen, 1988), produced by the patients for the swallow. A weaker activity of the anterior temporal muscle in swallowing water Shan in swallowing saliva is in accordance with findings in a previous study of the swallowing activity of jaw closing muscles (Tallgren & Tryde, 1991. In this connection it is interesting to note that Pamir & Kalipcilar (1988) in strain gauge measurements of functional forces on the complete upper denture found that lesser forces were excerted during swallowing water than during swallowing saliva.…”
Section: Discussionsupporting
confidence: 89%
“…No significant differences in amplitude or duration of the lip activity were found between swallowing with the old and the new dentures. Pamir & Kalipcilar (1988) studied the functional forces exerted on maxillary complete dentures by means of strain gauges. They found that greater forces were exerted on the upper denture during voluntary swallowing of saliva than during swallowing of water.…”
Section: Introductionmentioning
confidence: 99%